SISTEM INFORMASI DONASI BERBASIS MOBILE ANDROID PADA LEMBAGA DANA SOSIAL AL-JIHAD (DASA) MELALUI INTEGRASI CODEIGNITER DAN FLUTTER - Nur Arif, Aditya (STMIK Catur Sakti Kendari, 2024)
Digital donation management systems have been widely implemented in various organizations and companies. Numerous studies have been conducted regarding digital donation management, and one popular approach involves leveraging website technology. This research aims to construct a donation information system for the Dana Sosial AL-Jihad Institution (DASA) through the integration of CodeIgniter and Flutter, based on the Android mobile platform. The CodeIgniter backend framework and Flutter frontend are employed to develop and implement the Android-based donation retrieval information system. While Flutter is chosen for its attractive and responsive UI, CodeIgniter is selected for its capacity to easily manage donation business logic and databases. In this study, the SDLC Waterfall method is adopted as the approach for system development. The SDLC Waterfall steps encompass requirement analysis, system design, implementation, testing, and development. The outcomes of this research will aid the DASA institution in efficiently and swiftly managing donation data. The developed information system can facilitate data sharing processes, locate donor addresses, and generate reports regarding donation outcomes. Consequently, the DASA institution can achieve its goals of providing social assistance to the less privileged community.